UNEMPLOYMENT AMONG YOUTHS AND ITS IMPACT ON LOCAL SOCIO-ECONOMIC DEVELOPMENT IN YOLA SOUTH, ADAMAWA - Gambo, Ibrahim Musa (Ayden International Journal of Education and Social sciences, 2025)
This study is on “socio-economic effects of youth’s unemployment in Yola South Local Government Area of Adamawa State”. It is a common fact that youth unemployment is becoming a threat to the economic development in Nigeria. The stu dy examines the effects of youth unemployment in Nigeria on the economic development and its resultant consequences. The study aimed to identify whethe r high rate of poverty and crime are recorded as a result of unemployment. The study employed the primary data where information was collected from various individuals in Yola South Local Government Area of Adamawa State whom are mostly youth. Responses from 500 questionnaires analysed using simple percentage and chi-square was used to test the hypothesis. The result from the study reveals that youths are involved in drugs abuse, criminal activities and increased rate of poverty among other things. Thus, unemployment had adverse effects on the nation’s socioeconomic development and therefore reduces the standard of living. Based on the finding, it was proffered that the employment scheme and other manpower skills development programmes should be designed to reduce the unemployment rate in the country. Government should establish more industries in order to cre ate more jobs for the teeming youths. Sensitizations on the dangers of drug abuse need to be intensified by the relevant government agencies